Diagnostic Potential of Pulsed Arterial Spin Labeling in Alzheimer's Disease - Trebeschi, Stefano; Riederer, Isabelle; Preibisch, Christine; Bohn, Karl P.; Förster, Stefan; Alexopoulos, Panagiotis; Zimmer, Claus; Kirschke, Jan S.; Valentinitsch, Alexander (Frontiers in Neuroscience, 2016)
Alzheimer’s disease (AD) is the most common cause of dementia. Although the underlying pathology is still not completely understood, several diagnostic methods are available. Frequently, the most accurate methods are also the most invasive. The present work investigates the diagnostic potential of Pulsed Arterial Spin Labeling (PASL) for AD: a non invasive, MRI-based technique for the quantification of regional cerebral blood flow (rCBF). In particular, we propose a pilot computer aided diagnostic (CAD) procedure able to discriminate between healthy and diseased subjects, and at the same time, providing visual informative results. This method encompasses the creation of an healthy model, the computation of a voxel-wise likelihood function as comparison between the healthy model and the subject under examination, and the correction of the likelihood function via prior distributions. The discriminant analysis is carried out to maximize the accuracy of the classification. The algorithm has been trained on a dataset of 81 subjects and achieved a sensitivity of 0.750 and a specificity of 0.875. Moreover, in accordance with the current pathological knowledge, the parietal lobe and limbic system are shown to be the main discriminant factors.